2020
DOI: 10.1149/1945-7111/ab6c57
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Local pH Value Changes of Acidic Aqueous Zinc Ion Batteries with a Manganese Dioxide Electrode during Cycling

Abstract: The research on aqueous zinc ion batteries (AZIB) is getting more attention as the energy transition continues to develop and the need for inexpensive and safe stationary storage batteries is growing. As the detailed reaction mechanisms are not conclusively revealed, we want to take an alternative approach to investigate the importance of pH value changes during cycling. By adding a pH-indicator to the electrolyte (2 M ZnSO 4 + 0.1 M MnSO 4 ), the local pH-value change during operation is visualized in operand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
129
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(132 citation statements)
references
References 49 publications
(73 reference statements)
3
129
0
Order By: Relevance
“…Because relying on protoncoupled electron transfers, this reaction is associated with significant local pH gradients, triggering precipitation of zinc hydroxides and restricting the gravimetric capacity, as well as to potential drifts. [10][11][12][13] To overcome these limitations, Mateos et al demonstrated the benefit of using a buffered aqueous electrolyte (pH = 5) to fully convert MnO 2 to water-soluble Mn 2+ (aq) at stable potential values and with low hysteresis through the highly reversible proton-coupled reaction given below: where AH and A are the weak Brønsted acid and base of the buffer, respectively. When performed on transparent 2D ITO electrodes, accumulation of an electrochemically inactive fraction of MnO 2 (ca.…”
Section: -3mentioning
confidence: 99%
“…Because relying on protoncoupled electron transfers, this reaction is associated with significant local pH gradients, triggering precipitation of zinc hydroxides and restricting the gravimetric capacity, as well as to potential drifts. [10][11][12][13] To overcome these limitations, Mateos et al demonstrated the benefit of using a buffered aqueous electrolyte (pH = 5) to fully convert MnO 2 to water-soluble Mn 2+ (aq) at stable potential values and with low hysteresis through the highly reversible proton-coupled reaction given below: where AH and A are the weak Brønsted acid and base of the buffer, respectively. When performed on transparent 2D ITO electrodes, accumulation of an electrochemically inactive fraction of MnO 2 (ca.…”
Section: -3mentioning
confidence: 99%
“…S9), respectively, whereas the liquid one delivers a clearly dissolved feature compared to HCCE (Fig. 3c), which may be caused by the severe Mn dissolution and exacerbated by the acute acid due to local pH fluctuation as the previous study reported [36]. To further analyze, the ex-situ Transmission electron microscopy (TEM) test of cathode discharged to 0.8 V after being cycled with HCCE and liquid was performed.…”
Section: Analysis Of Cathode Of Zn/mno 2 Batterymentioning
confidence: 85%
“…[30,97] However, many previous works have indicated that the storage mechanism in AZIBs would be also greatly influenced by the properties of aqueous electrolyte, such as pH value, and the species of additive and Zn-salts, thus making the actual reaction process more complicated, and many controversial issues are still remaining. [99][100][101] Excepting the Zn 2+ , H + would also exists in the acidic electrolyte, such result would lead to a competitive reaction mechanism between Zn 2+ and H + during the charging and discharging process. [102] Until now, several types of mainstream storage mechanisms have been formally proposed, which can be included as follows: 1) Zn 2+ insertion/extraction mechanism; 2) ions/molecules co-insertion/extraction mechanism; 3) H + insertion/extraction mechanism; and 4) conversion reaction mechanism.…”
Section: Storage Mechanism Of Cathode Materialsmentioning
confidence: 99%